Готи в І—VII ст.: територія розселення та просування за археологічними джерелами - Бірбрауер, Ф. (Археологія, 1995)
Відмінності між оксівською та вельбарекою культурами, а також повідомлення Йордану породили історіографічну традицію про переселення племені готів зі Скандинавії до району Нижньої Вісли. Аналіз археологічних матеріалів дозволяє говорити лише про обмежену міграцію через море, яка суттєво не вплинула на місцеві народи. Незважаючи на єдність вельбарської культури в І—ІІ ст., є можливість виділення на її території областей, заселених не лише готами, а й іншими німецькими племенами (гепіди, ругії). Освоєння готами Волині, а потім більш південних областей України та Молдови (2-а область експансії) розпочалося на межі раннього та пізнього римських періодів із вторгнення малих груп, які утворили тут «формативну фазу» черняхівської культури. Про місця перебування остготів у V ст. судити важко через однаковість східнонімецьких старожитностей між Чорним морем і Середнім Подунав'ям. Различия между оксывской и вельбарекой культурами, а также сообщения Иордана породили историографическую традицию о переселении племени готов из Скандинавии в район Нижней Вислы. Анализ археологических материалов позволяет говорить только об ограниченной миграции из-за моря, которая существенно не повлияла на местные народы. Несмотря на единство вельбарской культуры в І—II вв., имеется возможность для выделения на ее территории областей, заселенных не только готами, но и другими германскими племенами (гепиды, ругии). На протяжении фаз В2 и В2/С1 (конец I — рубеж II/III вв.) вельбарское население продвигается на юго-восток Польши (1-я область экспансии). Здесь происходит процесс ассимиляции местного пшеворского населения. Часть прежней территории была покинута, а оставшийся заселенным восточный район Нижней Вислы можно связывать с племенем гепидов. Освоение готами Волыни, а затем более южных областей Украины и Молдовы (2-я область экспансии) началось на рубеже раннего и позднего римских периодов с вторжения малых групп, которые образовали здесь «формативную фазу» черняховской культуры. Стабилизация оседлости приходится на фазу С2 (260/270—300 гг.). Проблема автохтонного населения на Черняховской территории остается неясной. На основании письменных источников большую часть черняховской культуры можно связывать с грейтунгами-остроготами, а культуру Сынтана де Муреш (в Румынии) — с тервингами-везиготами. Черняховская культура прекратила существование в фазе СЗ (по Й. Тейралу — к 370/80 гг.), что связано с гибелью Остготской державы в результате гуннского нашествия. Генетически родственные черняховским некрополи Черноморского побережья, Крыма и Северного Кавказа (т. е. периферийных и смежных с Черняховским ареалом областей) продолжают функционировать и позже (до второй половины V в,). Они связаны с группами готов, оставшихся в Восточной Европе под гуннским господством. О местах пребывания остготов в V в. судить трудно из-за единообразия восточногерманских древностей между Черным морем и Средним Подунавьем. В Италии подобные находки конца V—VI вв. надо соотносить не только с остготами, прибывшими в 488 г. под предводительством Теодориха, но и со скирами Одоакра, переселившимися в 469/470 г. Однако, постоянные черты, присущие только готам, сохраняются и здесь. Это отсутствие оружия (а часто и иного инвентаря) в мужских погребениях, традиционные украшения — парные фибулы на плечах. Период истории вестготов между концом Черняховской (Сынтана де Муреш) культуры и завоеванием Иберийского полуострова (494—497 гг.) археологически не прослежен, включая время существования Толозианского государства в Аквитании (418—507 гг.). В Испании ряд некрополей археологически надежно связывается с вестготами до второй половины VI в. Процес слияния германцев и местных романцев завершился появлением в письменных источниках конца VII в. названий «испанцы» и «Испания». Differences between Oxyviar and Velbarian cultures, as well as Jordan’s information gave rise to a historiographical tradition about migration of the Gothic tribe from Scandinavia to the Lower Vistula region. An analysis of archaeological findings confirms only restricted migration from Scandinavia which exerted no significant effect on native peoples. Despite the unity of Velbarian culture in the lst-2nd cent., it is possible to identify in its territory some regions populated not only by Gotbs, but by other German tribes (hepids, rugia). During phases B2 and B2/C1 (end of the 1st cent, and the 2nd/3d cent) the Velbarian population moves towards the south-east of Poland (the 1st region of expansion). Here assimilation of the native pshevorskian population takes place. They left a part of the territory and the populated eastern region of the Lower Vistula territory may be associated with a tribe of hepids. Assimilation of Volyn and further of more southern regions of Ukraine and Moldova by Goths (the 2nd region of expansion) began at the border of the early and late Roman periods with invasion of small groups which formed there a «formative phase» of Chemyakhov culture. Stabilization of the settled way of life took place at phase C2 (260/270—300). A problem of autochthonous population in the Chernyakhov territory still remains vague. Written sources permit attributing most part of Chernyakhov culture to Greytung-Austrogoths, and Syntan de Muresh culture (in Romania) to the Therwings- Vesigoths. Chernyakhov culture ceised existing at the C3 phase (by 370/380 according to J. Theiral), which is a result of a fall of the Ostgothic state as a result of the Hunnish invasion. Necropoles of the Black Sea coast, Crimea and Northern Caucasus (i. e. the regions peripheral and contiguous to the Chernyakhov area) genetically affine to the Chemyakhov necropoles continued functioning later (till the second half of the 5th cent.). They are associated with groups of the Goths who remained in Eastern Europe under the supremacy of the Hunns. It is difficult to dwell on places of habituation of Ostgothes as East-German relics in the territory between the Black Sea and the Mid Danube are rather similar. In Italy findings of that kind are to be attributed not only to the Ostgothes who came in 488 under the command of Theodorich, but also to the Skyrians of Odoachr who migrated there in 469/470. Persistent attributes intrinsic only to the Goths are, however, preserved there: absence of armament (often also of other stocks) in male barrows, conventional adornment as paired fibules on the shoulders. The period of history of the Westgoths between the end of Chernyakhov (Syntan de Muresh) culture and conquest of the Iberian peninsula (494— 497) is not archacologically traced, the period of the Tolozan state existence in Aquitania (418—507) included. In Spain a series of necropoles is reliably associated with the Westgoths till the second half of the 6 th cent. The process of confluence of the Germans and native Romans was over when such terms as «Spaniards» and «Spain» appeared in written sources of the late 7th cent.